2015
DOI: 10.1038/ncomms9406
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-powered kHz rotation of a hemithioindigo-based molecular motor

Abstract: Photodriven molecular motors are able to convert light energy into directional motion and hold great promise as miniaturized powering units for future nanomachines. In the current state of the art, considerable efforts have still to be made to increase the efficiency of energy transduction and devise systems that allow operation in ambient and non-damaging conditions with high rates of directional motions. The need for ultraviolet light to induce the motion of virtually all available light-driven motors especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
216
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(226 citation statements)
references
References 43 publications
(46 reference statements)
4
216
2
4
Order By: Relevance
“…For example, the second-generation overcrowded-alkene motors, the hemithioindigo motor of Dube and co-workers [29] and the N-alkyl imine motors of Lehn and co-workers [32,33] all contain a (single) stereocenter. Owing to the stereocenter, the respective excited-state PES is asymmetric with respect to the two possible directions-CW or CCW-for the Z/E photoisomerizations that underlie the light-induced rotary motion.…”
Section: Other Mother Designs: Fewer Chiral Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the second-generation overcrowded-alkene motors, the hemithioindigo motor of Dube and co-workers [29] and the N-alkyl imine motors of Lehn and co-workers [32,33] all contain a (single) stereocenter. Owing to the stereocenter, the respective excited-state PES is asymmetric with respect to the two possible directions-CW or CCW-for the Z/E photoisomerizations that underlie the light-induced rotary motion.…”
Section: Other Mother Designs: Fewer Chiral Featuresmentioning
confidence: 99%
“…As for rotary speed, it was reported that 3 is capable of kHz frequencies at ambient temperatures. [29] The dibenzofulvene motors, in turn, lack a stereocenter but incorporate an axially chiral trityl moiety. Designed and synthesized by Bell and co-workers, [30,31] these systems appear promising motor candidates because their Z/E photoisomerizations around the central double bond are unidirectional and can attain high quantum yields (QYs) by appropriate substitutions (X in motor 4).…”
Section: R Ota R Y M Ol Ecu L a R Mot Orsmentioning
confidence: 99%
See 1 more Smart Citation
“…Directional movement has been demonstrated in artificial molecular machines (1)(2)(3)(4), using photoexcitation (5)(6)(7)(8)(9)(10)(11) and/or the sequential addition of chemical reagents (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and an autonomous chemically-driven molecular rotary motor that operates through a bio-inspired (23) information ratchet mechanism has been described (24,25). Here we report on an alternative class of ratchet mechanism, based on acid-base oscillations, that powers both rotary and linear molecular motors.…”
mentioning
confidence: 99%
“…An important factor in the enhanced performances of this metasurface comes from the blackbody nature of the nanoparticles, whose darkness is maintained regardless light input conditions, [29] yielding an extremely high thermal efficiency. The combination of excellent stability to saline corrosion, [35] large scale fabrication, [30] ultralight weight (only 3.8 g of gold for 1 m 2 of metasurface) and 98% recyclability provides an ideal platform for solar steam generation in both industrial and academic oriented applications, which range from large scales desalination power plants and sterilization systems to steamdriven nanorachets, [42][43][44][45] demonstrating new possible concepts of plasmonic blackbody materials that could enrich our world in innovative ways.…”
Section: Discussionmentioning
confidence: 99%